2009
DOI: 10.1016/j.jacc.2009.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Global Arginine Bioavailability and Increased Arginine Catabolism as Metabolic Profile of Increased Cardiovascular Risk

Abstract: Objective We hypothesized that an integrated assessment of arginine with its catabolic products may better predict cardiovascular risks than arginine levels alone. Background Arginine is the sole nitrogen source for nitric oxide (NO) synthesis. The major catabolic products of arginine are ornithine and citrulline. Methods Plasma levels of free arginine, ornithine, citrulline and the endogenous NO synthase inhibitor asymmetric dimethylarginine (ADMA) were measured using LC/MS/MS. We examined the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
172
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(181 citation statements)
references
References 27 publications
6
172
1
2
Order By: Relevance
“…HDL-C and triglyceride (TG) concentrations were measured on the Abbott ARCHITECT platform (Abbott Laboratories, Inc., Abbott Park, IL) as described (23,24). In the PAH population and a subset of control subjects, glucose, insulin levels, and highsensitivity C-reactive protein (CRP) were also measured with the Abbott ARCHITECT platform.…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…HDL-C and triglyceride (TG) concentrations were measured on the Abbott ARCHITECT platform (Abbott Laboratories, Inc., Abbott Park, IL) as described (23,24). In the PAH population and a subset of control subjects, glucose, insulin levels, and highsensitivity C-reactive protein (CRP) were also measured with the Abbott ARCHITECT platform.…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…3 Low arginine bioavailability may further compromise NO generation due to NO synthase uncoupling. 9,16 Since we first reported an association of low global arginine bioavailability with mortality in SCD, 11 low arginine bioavailability has subsequently been linked to mortality risk in both malaria 17 and cardiovascular disease in general, 14 and represents a novel biomarker of vasculopathy independent of genotype. Intravascular hemolysis also has the potential to drive a pro-coagulant state, as NO has the properties of inhibiting platelet activation, tissue factor expression and thrombin generation.…”
Section: Mechanisms Of Vasculopathymentioning
confidence: 99%
“…Patients with obstructive CAD had a lower global arginine bioavailability ratio (defined as arginine/[ornithine þ citrulline] versus plasma L-arginine levels) than those without obstructive CAD. 50 After adjusting for Framingham risk score, the lower global arginine availability ratio (but not L-arginine levels) and higher L-citrulline levels remained associated with the prevalence of obstructive CAD; global arginine availability ratio and ADMA showed a negative correlation. The global arginine availability ratio appears to serve as a more comprehensive concept of reduced NO synthetic capacity compared with systemic L-arginine levels.…”
Section: 23mentioning
confidence: 86%
“…The global arginine availability ratio appears to serve as a more comprehensive concept of reduced NO synthetic capacity compared with systemic L-arginine levels. Therefore, Tang et al 50 suggested that diminished arginine bioavailability ratio and high citrulline levels are associated with development of obstructive CAD and heightened long-term risk for major adverse cardiovascular events.…”
Section: 23mentioning
confidence: 99%